2000
DOI: 10.1016/s0002-9270(00)00977-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term use of mesalamine (Rowasa) suppositories in remission maintenance of ulcerative proctitis

Abstract: The results demonstrate that mesalamine suppositories are efficacious, well tolerated, and safe for the long-term maintenance of remission of ulcerative proctitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Trials of duration less than or equal to 4 weeks [11,12,20,30,51,58,67,111,112] were associated with lower response rate (11.3%) than trials of duration greater than 4 weeks (23.8%) [28,40,45,46,74,78,92]. In the multivariate analysis also the placebo endoscopic remission rate was significantly influenced by duration of trial (P = 0.0013).…”
Section: Endoscopic Remissionmentioning
confidence: 85%
“…Trials of duration less than or equal to 4 weeks [11,12,20,30,51,58,67,111,112] were associated with lower response rate (11.3%) than trials of duration greater than 4 weeks (23.8%) [28,40,45,46,74,78,92]. In the multivariate analysis also the placebo endoscopic remission rate was significantly influenced by duration of trial (P = 0.0013).…”
Section: Endoscopic Remissionmentioning
confidence: 85%
“…Mesalamine suppositories have been the mainstay of treatment in these patients [669], with efficacy and safety data superior to corticosteroid preparations [392]. Suppository dosing is typically nightly (twice or three times a day in more refractory patients) (Table 57.6).…”
Section: Ulcerative Proctitismentioning
confidence: 99%
“…However, accumulating data support the effectiveness of rectally administered treatments for the maintenance of remission in UP. In a placebo-controlled trial [40] , a significantly higher rate of remission maintenance was found in patients treated with mesalazine suppository (500 mg b.i.d.). Subsequent studies demonstrated the superiority of rectally administered treatment in maintenance of remission, even when used intermittently [41,42] .…”
Section: Maintenance Therapymentioning
confidence: 96%